Towards a prosodic model for Tiberian Hebrew: An intonation-based analysis - Pitcher, Sophia L. (Stellenbosch Papers in Linguistics Plus, 2022)
This study advances a preliminary framework for conceptualising the prosodic nature and structure of Tiberian Hebrew (TH) represented by the ṭaʿămê hammiqrāʾ through an analysis of an extant Ashkenazi cantillation tradition. The ṭaʿămê hammiqrāʾ (lit. “the senses of the reading [viz. Scripture]”) are notations added by medieval scribes to the written text of the Hebrew Bible to preserve and transmit its oral performance. Modern prosodic theory and the musical concept of conjunct and disjunct melodic motion are used to demonstrate that the ṭaʿămê hammiqrāʾ have a highly structured iconic and intonational basis that organises the system and conforms substantially to Selkirk’s (2000, 2009) cross-linguistic prosodic hierarchy. The intonation-based prosodic model proposed in this study offers a solution to the limitation Dresher (1994, 2013; see also Dresher and DeCaen 2018; DeCaen and Dresher 2020) encounters with the intonational phrase domain of his prosodic model, permitting an alternative analysis of so-called pausal forms as lengthened forms, which can occur at prosodic phrase boundaries regardless of pause. The intonation-based model is tested by assessing how accurately it reflects the cross-linguistic prosodic features of restrictive and nonrestrictive relative clauses. The results indicate that TH distinguishes three prosodic classes of relatives—prosodically marked restrictives, prosodically marked nonrestrictives, and prosodically undifferentiated relatives—findings that accord with Birkner’s (2012) intonation-based study of the prosodic structure of German relative clauses.